Implementation Of Arabic Bowling Model For Mastery Of Mahārah Kalām In Arabic Language Learning In Al-As’adiyah Integrated Madrasah Aliyah Sered Madukara Banjarnegara - Wafiq Nahda, Aida; Mu'tafi, Ali; Faturrokhman, Faturrokhman (DAS Institute, 2024)
In completing this research, the author conducted a study using a qualitative approach, where the type of research is field research. The results of the study showed that learning begins with repeating takror and adding vocabulary, then students form groups, each group takes turns to roll the ball towards the Arabic bowling bottle, after that the students open the hard sheet (questions) that correspond to the material that day, after that the students answer the questions verbally in Arabic and the teacher gives marks on courage, nahwu / sharf, lafadz, vocabulary and fluency. Supporting factors for the use of the Arabic bowling model include student enthusiasm for learning, fun games, peer support, and cooperation between teachers, students, and the madrasah.